Peran Perpustakaan dalam Membantu Riset tentang Studi Islam di Indonesia - Nova Irawati, Sutiyah; Fitriyanti, Nur; Nugroho, Prasetyo Adi (Perpustakaan Universitas Gadjah Mada, 2025)
Islamic education in Indonesia has a long history, with significant contributions from previous scholars. Librarians have a role in helping academics in advancing Islamic studies. observing how the role and contribution of libraries and their librarians in helping Islamic studies in academic environments. This study uses a qualitative method using metadata from Scopus. There are around 133 documents found. Then the documents are sorted to remove documents that do not use English and documents in the form of reviews. There are around 91 documents left from 2008-2024. The data sample was analyzed using bibliometric and SLR methods. The results show that the most used words in the keywords of previous papers are Muhammadiyah and Syatibi. Both words are connected to the word’s mayor, Indonesian and Islam. Research on Islamic studies involves or is related to Muhammadiyah as the largest Islamic organization in Indonesia besides Nahdlatul Ulama (NU).